MONITORING CORN DISEASES IN POLTAVA REGION - Pospielov, S. V.; Pospielova, G. D.; Nechiporenko, N. I.; Kovalenko, N. P.; Ochrimenko, V. V. (Scientific Progress & Innovations, 2021)
In recent years, there has been the tendency to increase in the air temperature background during the year, sharp fluctuations of humidity, and the manifestation of extreme weather phenomena, as a result of which plants are under stress, which leads to reduced plant resistance to pests. Therefore, the adaptation of agriculture to current and future climate change is crucial. In such conditions, the maximum realization of plant productivity potential, ensuring high quality of seeds and ecological purity of products require the strengthening of phyto-sanitary control measures in the system of integrated plant protection. The aim of our research was to conduct phyto-sanitary monitoring of corn crops of Liubava 279 MV, Bilozirsky 295 SV, Soloniansky 298 SV and Dniprovsky 257 SV hybrids during the growing seasons of 2019–2021 in Poltava region. The scale proposed by H.V. Hrytsenko and Ye. L. Dudka was used to assess the degree of damage to corn leaves and stems (intensity of disease manifestation). Such crop dominant diseases were detected: common and loose smut, fusarium root rot and fusarium head blight. The degree of spreading and intensity of pest development on maize hybrids was established. The susceptibility of plants of Dniprovsky 257 SV hy- brid to the pathogen of common smut and resistance to this type of infection in Bilozirsky 295 SV hybrid were determined. The tendency to increase the spreading of loose smut on all corn hybrids over the years of research was observed. The lowest level of susceptibility was observed in Bilozirsky 295 SV hybrid. Accord- ing to the results of the monitoring, fusarium root rot was detected on maize plants of all the studied hybrids, which confirms the direct dependence of the infection development on weather conditions. During the years of research under different hydrothermal conditions, fusarium root rot on maize of the tested hybrids was registered at the level of 1.2–4.8 %, which indicated both the presence of seed infection and high saturation of agrocenoses with fusaria in the studied area. The analysis of the microbiota of corn ears demonstrates a significant infection of the grain with fungi of Fusarium, Penicillium, and Aspergillus genera. The lowest level of contamination was found in Belozirsky 295 CV hybrid with 22 % of corn ears infected with Fusaria, 1.8 % of ears – with Penicillia, and there were no symptoms of Aspergilla infestation. It is necessary to systematically monitor diseases in maize areas in order to plan, develop and determine the expediency of conducting preventive and treatment measures for plant protection.